2015
DOI: 10.1016/j.ijnonlinmec.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A thermal non-equilibrium model with Cattaneo effect for convection in a Brinkman porous layer

Abstract: a b s t r a c tThis paper aims to investigate the onset of thermal convection in a layer of fluid-saturated Brinkman porous medium taking into account fluid inertia and local thermal non-equilibrium (LTNE) between the solid and fluid phases with Cattaneo effect in the solid. A two-field model is used for the energy equations each representing the solid and fluid phases separately. The usual Fourier heat-transfer law is retained in the fluid phase while the solid phase is allowed to transfer heat via a Cattaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…To understand the heat transfer characteristics in a FF-saturated porous medium, FTC in a porous medium has also been studied extensively (Sekar et al [11], Shivakumara et al [12,13], Nanjundappa et al [14,15,16]). Besides, the implications of additional effects such as magnetic field dependent viscosity (Nanjundappa et al [17,18], Shivakumara et al [19,20]), rotation (Shivakumara et al [21], Nanjundappa et al [22]), internal heating (Nanjundappa et al [23,24]), throughflow (Nanjundappa et al [25]), non-uniform basic temperature gradients (Nanjundappa et al [26]), local thermal nonequilibrium (Shivakumara et al [27,28,29,30]), Cattaneo heat flux law (Shivakumara et al [31,32]) have also been investigated on FTC in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the heat transfer characteristics in a FF-saturated porous medium, FTC in a porous medium has also been studied extensively (Sekar et al [11], Shivakumara et al [12,13], Nanjundappa et al [14,15,16]). Besides, the implications of additional effects such as magnetic field dependent viscosity (Nanjundappa et al [17,18], Shivakumara et al [19,20]), rotation (Shivakumara et al [21], Nanjundappa et al [22]), internal heating (Nanjundappa et al [23,24]), throughflow (Nanjundappa et al [25]), non-uniform basic temperature gradients (Nanjundappa et al [26]), local thermal nonequilibrium (Shivakumara et al [27,28,29,30]), Cattaneo heat flux law (Shivakumara et al [31,32]) have also been investigated on FTC in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [29] studied the MHD flow over a cone and a wedge with the Cattaneo-Christov heat flux model and shows that the heat transfer rate in the fluid flow over a cone is higher than that of the flow over a wedge. Further, numerous researchers [30][31][32][33][34][35] used the Cattaneo-Christov heat flux model to formulate energy equations and discuss the flow and heat transfer phenomenon for different types of non-Newtonian fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Haddad [33] examined the heat flux in a Brinkman porous channel embedded with fluid inertia. Shivakumara et al [34] observed the thermal convection with Cattaneo effects in the solid and found that its impacts on the nature of convective instability are efficient. Mustafa et al [35] studied the rotating flow upon linearly stretching disk.…”
Section: Introductionmentioning
confidence: 99%